2012
DOI: 10.1007/s12603-012-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Fewer referrals to Swedish emergency departments among nursing home patients with dementia, comprehensive cognitive decline and multicomorbidity

Abstract: Objectives:The objective was to describe the extent to which nursing home patients had cognitive impairments and were diagnosed with dementia. Furthermore, to describe and compare multicomorbidity, health status and drug use in the three subgroups; dementia diagnosis/not referred, dementia diagnosis/referred and no dementia diagnosis/not referred to an emergency department (ED) over a one-year period. Methods: A crosssectional follow-up study was carried out in Sweden. RAI/MDS assessments were conducted on 719… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…12 This review identified only 1 low-quality study that investigated medication type. 46 Given this evidence gap and potential impact of medications on ED attendance, further research is indicated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 This review identified only 1 low-quality study that investigated medication type. 46 Given this evidence gap and potential impact of medications on ED attendance, further research is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…There was high-strength evidence that neuropsychiatric symptoms, including depression, were associated with increased ED attendance. 16,28,46 Although included studies did not specify any other behavioral or psychological concerns, there is complementary evidence of hospitalizations associated with neuropsychiatric symptoms, 11 including depressed mood. 2,7 As well as carer distress, 64 neuropsychiatric symptoms are associated with complications such as falling and treatment noncompliance, 65 which may also precipitate ED attendance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigators have primarily examined characteristics and treatment of single disease states or use of single drug classes in both U.S. (59). and European studies of aggregate nursing home data (1012). The most recent National Nursing Home Survey collected comprehensive medical data including up to sixteen current diagnoses and provides the data necessary to investigate patterns of co-morbid conditions in a nationally representative sample of U.S. nursing home residents (13).…”
Section: Introductionmentioning
confidence: 99%